PELAKSANAAN PASAL 48 PERATURAN MENTERI SOSIAL NOMOR 1 TAHUN 2018 TENTANG EVALUASI PENERIMA MANFAAT PROGRAM KELUARGA HARAPAN DI DESA UJUNG GADING - Lili Yani Harahap (Program Studi Hukum Tata Negara (Siyasah) IAIN Palopo, 2024)
This research is to determine the implementation of Article 48 of the Minister of Social Affairs Regulation Number 1 of 2018 concerning the Evaluation of Beneficiaries of the Family Hope Program and to determine the implementation of membership graduation for the beneficiaries of the Family Hope Program in Ujung Gading village, Sihapas Barumun subdistrict, Padang Lawas Regency. The type of research used is qualitative descriptive research. Data collection methods include observation, interviews, and related documents. The data collected goes through the analysis, editing, verification, and analysis stages. The research showed that implementing Minister of Social Affairs regulation number 1 of 2018 article 48 concerning the evaluation of beneficiaries of the Family Hope Program in Ujung Gading village, Padang Lawas district, was considered successful. Ministry of Social Affairs regulations carry out the implementation and stages recommended by the government. Implementing participant evaluation and graduation still has many shortcomings and irregularities, especially because many PKH recipient participants are considered to be from within the village head's closest circle.